2017
DOI: 10.3390/environments4010023
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality Assessment and Study of Different VOC Contributions within a School in Taranto City, South of Italy

Abstract: Children spend a large amount of time in school environments and when Indoor Air Quality (IAQ) is poor, comfort, productivity and learning performances may be affected. The aim of the present study is to characterize IAQ in a primary school located in Taranto city (south of Italy). Because of the proximity of a large industrial complex to the urban settlement, this district is one of the areas identified as being at high environmental risk in Italy. The study carried out simultaneous monitoring of indoor and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Besides CO 2 pollutants, exposure to volatile organic compound has been a concern of Indoor Environment Quality (IEQ) in the schools and other buildings. VOC in the school environment shows lower level in a large room and good ventilation classroom with low occupancy ratio (Marzocca et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Besides CO 2 pollutants, exposure to volatile organic compound has been a concern of Indoor Environment Quality (IEQ) in the schools and other buildings. VOC in the school environment shows lower level in a large room and good ventilation classroom with low occupancy ratio (Marzocca et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…It was concluded that the higher concentration of benzene in the kindergarten located in the industrial region is due to the contribution from the petrochemical plant (Villanueva et al., 2018). In naturally ventilated school buildings at Taranto City, South of Italy, three classrooms were selected for benzene monitoring and the average concentration found in all the three were 0.44 μg/m 3 which was less than the outdoor ambient benzene levels (0.67 μg/m 3 ) (Marzocca et al., 2017). In Czech technical university in Prague, the average level of benzene in indoor air was 1.6–4.9 μg/m 3 during June 2012 (Kolarik et al., 2015).…”
Section: Indoor Benzene Concentrationmentioning
confidence: 99%
“…Household users are exposed to several pollutants. There are numerous source of pollution produced by the occupants and their activities, by the furniture and building materials, by technical defects, the presence of humidity or dirt, and, in particular, the use of chemicals (cleaning, hygiene, and personal care products) as well as tobacco smoke in smokers’ homes [ 31 , 32 , 33 , 34 ]. Pollution from outside such as pollen, dust, and industrial and traffic pollution must also be considered.…”
Section: Introductionmentioning
confidence: 99%